Heterosis and Combining Ability Analysis in Tomato Using Line × Tester Model - , Poornima Singh; , Ashok Kumar; , G.K Ahirwar (Archives of Current Research International, 2024)
The experiment entitled Heterosis and combining ability studies for yield and yield attributing trait in Tomato (Lycopersicon esculentum) in Bundelkhand Region was carried out during Rabi 2021-22 and 2022-23 at the Experimental, Organic Research farm Kargunwa ji, Jhansi, Department of Horticultural Sciences, Institute of Agricultural Sciences, Bundelkhand University Jhansi (Uttar Pradesh). The present experiment was design under Randomized block design with three replication with plot size - 3×3m and number of rows per plant – 5 rows per plant accommodating spacing (60×60) cm. All F1s (50) along with parents were raised in RBD in 3 replications and population size were 30 plants per treatment with standard spacing. All 17 parents (5 lines and 12 testers) were raised in separate plots along with a check grown in RBD in three replications to study the combining ability, to estimate the magnitude or percentage of heterosis in the crosses, for identification of the best F1 hybrid and correlation among different traits. Since, Line × tester analysis provides information of potential parents the hybrid line. The three best combinations for line parents viz., H-88-78-5, Kashi Aman, H-88-78-5 and their F1 hybrid viz., H-88-78-1x Kashi Chaya,VRT-67 × Kashi Chaya,H-88-78-5×VRT-50 performed significantly better amongst rest of the other treatment.